Implementation of The Muhadharah Program As An Effort To Enhance Maharah Al-Kalam At The Tahfidz Ulumul Qur’an Islamic Boarding School - Hotmanianti Siregar; Rahmaini Rahmaini (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study is motivated by the importance of speaking skills in learning Arabic, particularly in the environment of Islamic boarding schools and among the students who live there. However, many students still lack optimal speaking skills, making support programs such as muhadharah necessary. This study aims to examine the implementation of the muhadharah program as an effort to improve the maharah al-kalam of students at the Tahfidz Ulumul Qur’an Sei Rotan Islamic Boarding School. Developing Arabic speaking skills requires various programs that can foster courage, fluency, and self-confidence in speaking Arabic. The muhadharah program is one of the initiatives implemented to support the improvement of students’ Arabic speaking skills (maharah al-kalam) at the Ulumul Qur’an Sei Rotan Islamic Boarding School. This study employs a descriptive qualitative approach using case studies as its research method. The results of this study indicate that the implementation of the muhadharah program has a positive impact on the students’ maharah al-kalam. This is because the muhadharah program helps students improve their courage to speak in public, trains them in fluency of speech, and builds their self-confidence in communicating in Arabic. Thus, this muhadharah program plays a vital role in enhancing the students’ maharah al-kalam at the Tahfidz Ulumul Qur’an Sei Rotan Islamic Boarding School. The findings of this study also serve as a basis for evaluation or as a reference for the boarding school and for enriching the study of maharah al-kalam.